Keindahan dalam Hikayat Sultan Taburat - Adilah Nurul Hidayah (Masyarakat Pernaskahan Nusantara (The Indonesian Association for Nusantara Manuscripts, Manassa), 2020)
Hikayat Sultan Taburat written by Muhammad Bakir. Hikayat Sultan Taburat is one of adventure stories which is also included in the type of solace tale. This research used transliteration of Hikayat Sultan Taburat ML 259 version from Rias Anto Suharjo in 2019. Hikayat Sultan Taburat has a dominant aesthetic elements and function in it. Malay aesthetic theory by Bragunsky used to be able to reveal those purpose. The various elements of external aesthetic in Hikayat Sultan Taburat could be identified through the description of the beauty of clothing, the charm of the princess, garden, music, reception, warfare, ship, and the crowds of the country. The function of external aesthetic in Hikayat Sultan Taburat is to entertain the reader.